The Levels of Antibiotic Use in Tyfoid Fever Patients in Interna Wards at the Hospital Makassar City - Farid, Andi Muhammad; Saharuddin, Muh (Jurnal Farmasi Sandi Karsa, 2022)
Typhoid fever is an acute infectious disease of the small intestine caused by the bacterium Salmonella typhi (S.typhi) which is an endemic systemic infectious disease, which is transmitted through the food or drink consumed. Antibiotics are a group of drugs that are often used today to treat typhoid fever. The purpose of this study was to find out the most antibiotics used for the treatment of typhoid fever in internal care at the Makassar City Hospital, to find out the rational use of antibiotics which includes, the right drug, the right indication, and the right patient. This research is an observational study conducted retrospectively (non-experimentally) and analyzed using descriptive methods. Sampling by purposive sampling method. The study sample was typhoid fever patients who met the inclusion criteria, had no complications and had complete medical record data. The data is compared with the standard of medical treatment at Makassar City Hospital. The results showed that the most use of antibiotics in typhoid fever patients at the Makassar City Hospital's Internal Care for the period January-February 2022 consisted of Ciprofloxacin (50.8%), Ceftriaxone (19.6%), Cefixime (9.8%), Chloramphenicol (6.5%), Cotrimoxazole (6.5%) Levofloxacin (4.9%) cefotaxim (1.6). Evaluation of the use of antibiotics is known to be the right indication (100%), the right drug (100%), the right patient (100%). The high accuracy of the drug, the right indication and the patient's accuracy is because the hospital has used antibiotics that are in accordance with existing guidelines.